Subjective quality of life of informal caregivers aged 50–69 in Poland - Abramowska-Kmon, Anita; Maciejasz, Magdalena (Studia Demograficzne, 2018)
Providing informal care to adults, especially elderly people, may affect many aspects of caregivers’ life, such as: physical and mental health, financial situation, social contacts, etc. Supporting dependent seniors is associated to a higher level of stress, burden and depression as well as higher mortality. The main purpose of this paper is to analyse the relationship between caregiving for adults and the subjective quality of life among Poles aged 50–69. We took into account not only the fact of providing care to adult people, but also its beginning, continuation and ending between waves. We assumed that subjective quality of life may be expressed by two variables: one describing life satisfaction, and the second one – loneliness. We used the panel subsample from the Generation and Gender Surveys (GGS) carried out in Poland in 2010/2011 and in 2014. We found a negative effect of stopping caregiving between waves on wellbeing of women-carers, which may be related to the loss of a close person. Moreover, providing care for a longer period of time increases loneliness, which confirms that providing support to others may lead to isolation and smaller social networks.